The influence of planetary attractions on the solar tachocline - Callebaut, Dirk K. (2012)
We present a physical analysis of the occasionally forwarded hypothesis that solar variability, as shown in the various photospheric and outer solar layer activities, might be due to the Newtonian attraction by the planets. We calculate the planetary forces exerted on the tachocline and thereby not only include the immediate forces but we also take into account that these planetary or dynamo actions occur during some time, which demands integration. As an improvement to earlier research on this topic we reconsider the internal convective velocities and we examine several other effects, in particular those due to magnetic buoyancy and to the Coriolis force. The main conclusion is that in its essence: planetary influences are too small to be more than a small modulation of the solar cycle. We do not exclude the possibility that the long term combined action of the planets may induce small internal motions in the sun, which may have indirectly an effect on the solar dynamo after a long time.